Hydrogen production from CO2 reforming of methane over cobalt-based catalysts - Ji Siang, Tan (2015)
Increased concerns on anthropogenic greenhouse gas emissions have renewed interest in the CO2 (dry) reforming process as an alternative to steam reforming for synthesis gas production from natural gas. For hydrocarbon dry reforming, where the product stream H2:CO ratio is less than 3, synfuel production is more amenable and acceptable for downstream methanol and other oxygenated synthesis. However, dry reforming is highly endothermic, and suffers from carbon-induced catalyst deactivation. This thesis therefore investigates and evaluates the performance of methane dry reforming process at different operation conditions such as reaction temperature and feed composition, and the effects of loaded metals (Mo and Ni) on alumina-supported Co-based catalyst. Runs of the methane dry reforming experiment were conducted in a computer-controlled fixebed reactor at different feed compositions and reaction temperature. Both MoO3 and NiO phases were formed during wetness co-impregnation with a mixture of deionized water and alumina support as measured in X-ray diffraction. Temperature-programmed calcination showed that the transformations from MoO3 to CoMoO4 phase and NiO to NiAl2O4 phase were a 2 step process involving the formation of an oxidation intermediate form. Calcination of co-impregnated catalysts at 500 0C for 5 h appeared to be optimal preparation condition for H2 selectivity. Al2O3 support was the best support to give the highest H2 to CO ratio. Second metal promotion did not alter reaction rate significantly. However the interaction of loaded metal oxides with the surface carbonaceous species resulted in substantially reduced carbon deposition on Co-based catalyst, with Ni providing the greatest coking resistance compared to Mo. A quantitative relationship between activation energy and feed composition of CO2:CH4 ( 1:1, 2:1 and 3:1 ) as well as reaction temperatures (923 K, 953 K and 973 K) was obtained over bimetallic 5%Ni-10%Co/Al2O3 catalyst which gave the highest value of H2/CO ratio in the methane dry reforming process. Methane dry reforming activity was stable with time-on-stream for 4 h.